Optimization and simulation for sustainable supply chain design - Lucas Schreiber (Digital Transformation in Maritime and City Logistics: Smart Solutions for Logistics. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 28, 2019)
Purpose: This paper provides an overview of analytical optimization models and simulation-based approaches coping with upcoming challenges concerning the growing requirements within the field of sustainable supply chain design. It aims to combine the two highlighted solution methods in order to propose a holistic approach for decision-making support in this area. Methodology: Initially, a literature review on current application solutions for sustainable supply chain design is given. The regarded and analyzed approaches will be clustered and allocated to supply chain design tasks. Synergetic effects of combining simulation and optimization are identified and an integrated approach is outlined. Findings: Sustainable supply chain design tasks can be encapsulated in specific modules which are optimized simultaneously. Partial solutions are created which simplify the simulation model and reduce the necessary configurations to verify the robustness. Originality: Current approaches focusing on sustainable supply chain design mainly use simulation or optimization. A well-defined approach using various preceded optimizations for modularized strategic tasks like partner selection, allocation of resources or determination of transport relations with subsequent verification of the results in a simulation has not been proposed yet.
urn:nbn:de:gbv:830-882.054886; 10419/209197; https://econpapers.repec.org/RePEc:zbw:hiclpr:28
Keywords: 650; Supply chain design; Optimization; Simulation; Sustainability